Importance of play school in child development (International Journal of Scientific Research and Management (IJSRM), 2017)
A play school is a place where around 10-20 children spend 1-2 hours each day under the supervision of a couple of teachers. "The supervisor-child ratio should ideally be around 1:10". The play schools have a lot to offer, and that the play schools should not be aimed at developing academic skills like reading and writing. There should be no set goals or any stress on performance; the focus should be on the sensory-motor development and the social development of the child. I am very much an advocate of play schools since they develop age-appropriate behavior at the right time